Implementasi Model SIUUL dalam Mengembangkan Kemampuan Berceramah - Aprilia Rifani; Muhammad Ikhwan Hakim; Rayhan Saputra; Salsa Dsetantria; Wulan Nuriana; Sri Watini (FKIP, Universitas Palangka Raya, 2025)
The aim of this research is to describe the SIUUL model which is a speaking and reading learning model based on humanitarian philosophy, with stages of learning development based on Islamic values ​​and interpersonal intelligence in learning Public Speaking in giving lectures. This research is research using a qualitative approach in the form of observations directly and ask questions to the audience. The object of this research is through informants who provide research data through interviews and documentation. In implementing the SIUUL model, it is hoped that it can help individuals from various backgrounds to develop abilities in lecturing methods. With this technology-based approach, we can provide solutions that are more affordable and accessible to many people.